Association between Microvolt T-Wave Alternans and Malignant Ventricular Arrhythmias in Chagas Disease - Almeida,Bárbara Carolina Silva (2018)
Abstract Background: Sudden cardiac death is the most frequent death mechanism in Chagas disease, responsible for 55% to 65% of the deaths of patients with chronic Chagas cardiomyopathy (CCC). The most often involved electrophysiological mechanisms are ventricular tachycardia and ventricular fibrillation. The implantable cardioverter defibrillator (ICD) has a beneficial role in preventing sudden death due to malignant ventricular arrhythmias, and, thus the correct identification of patients at risk is required. The association of microvolt T-wave alternans (MTWA) with the appearance of ventricular arrhythmias has been assessed in different heart diseases. The role of MTWA is mostly unknown in patients with CCC. Objectives: To evaluate the association between MTWA and the occurrence of malignant ventricular arrhythmias in patients with CCC. Method: This is a case-control study including patients with CCC and ICD, with history of malignant ventricular arrhythmias (case group), and patients with CCC and no history of those arrhythmias (control group). The MTWA test results were classified as negative and non-negative (positive and indeterminate). The significance level adopted was a = 0.05. Results: We recruited 96 patients, 45 cases (46.8%) and 51 controls (53.1%). The MTWA test was non-negative in 36/45 cases (80%) and 15/51 controls (29.4%) [OR = 9.60 (95%CI: 3.41 - 27.93)]. After adjustment for known confounding factors in a logistic regression model, the non-negative result continued to be associated with malignant ventricular arrhythmias [OR = 5.17 (95%CI: 1.05 - 25.51)]. Conclusion: Patients with CCC and history of malignant ventricular arrhythmias more often have a non-negative MTWA test as compared to patients with no history of arrhythmia.